Proses Peninjauan Kembali Sebagai Wewenang Mahkamah Agung Berdasarkan Undang-Undang Kekuasaan Kehakiman - Yofi Permatasari; Andika Jinaratana; Rasji Rasji (Publikasi Indonesia, 2022)
The Supreme Court is the highest state court of all jurisdictions (general courts, religious courts, military courts and state administrative courts), which in carrying out their work must be free from government influence and other influences. Based on article 20 paragraph (2) of the Judicial Powers Act which clarifies that the authority of the Supreme Court is to adjudicate at the cassation level, judicial review, or other authorities listed within the provisions of the law. In the case of a court decision at the cassation level, the parties concerned may be inquired to return it to the Supreme Court, unless something else stipulated by law. The decision requested to be re-appeared must take under consideration certain conditions and mechanisms decided by law. Against the decision of justice once more can not be done recovery again.